The cellular selection mechanism for multi solution NP-hard optimization problems - Hossein Rajabalipour Cheshmehgaz, 1975-, author; Habibollah Haron, author; Muhammad Ikhwan Jambak, author; International Conference on Water Resources (ICWR 2009) (26-27 May : 2009 : Bayview Hotel, Langkawi, Kedah, Malaysia) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL